Preparation method of high-compaction and high-electrical-property iron phosphate

The preparation of lithium iron phosphate by a co-precipitation method with multi-stage concentration control and particle size distribution solves the problems of wastewater treatment difficulty and particle size instability caused by additives in the existing technology, and realizes high-compaction and high-electrical-performance lithium iron phosphate materials.

CN120943228APending Publication Date: 2025-11-14ZHEJIANG YOUSHAN NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511300538.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing technologies require the addition of complexing agents and template agents during the preparation of iron phosphate, which leads to difficulties in wastewater treatment, complex operations, unstable particle size distribution, poor product stability, and difficulty in controlling the formation of small particles, thus affecting electrical properties.

Method used

By employing a multi-stage concentration control and particle size distribution method, large, medium, and small particle iron phosphate is prepared in a co-precipitation method using large and small ion dopants. Combined with staged feeding and concentration gradient design, the reaction rate and crystallization process are controlled, avoiding the addition of additional additives.

Benefits of technology

The optimized distribution of iron phosphate particles was achieved, improving compaction density and electrical properties, making it suitable for industrial production. The compaction density of lithium iron phosphate reached over 2.55 g/cm³, and the 1C capacity reached 144.6-147.3 mAh/g, improving the ionic conductivity and cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120943228A_ABST
    Figure CN120943228A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of high-compaction and high-electrical-property iron phosphate, and belongs to the technical field of lithium ion batteries, and the preparation method comprises the following steps: S1, preparing an iron salt solution A, an iron salt solution B, a phosphorus salt solution A and a phosphorus salt solution B; s2, adding a doping agent A into the ferric salt solution A to obtain a doped ferric salt solution A; adding a doping agent B into the ferric salt solution B to obtain a doped ferric salt solution B; adding an oxidizing agent into the phosphorus salt solution A to obtain a phosphorus-oxygen mixed solution C; s3, adding the doped ferric salt solution A and the phosphorus-oxygen mixed solution C to generate an intermediate A; adding the doped ferric salt solution B and the phosphorus salt solution B to generate an intermediate B, so as to obtain mixed slurry D; s4, heat preservation; s5, washing, drying, calcining, demagnetizing and sieving to obtain high-compaction battery-grade iron phosphate; through multi-stage concentration control and grain composition, the prepared iron phosphate material has optimized grain distribution, and the compaction density can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a method for preparing high-pressure and high-electrical-performance iron phosphate. Background Technology

[0002] With the depletion of fossil fuels such as oil, coal, and natural gas, rechargeable lithium-ion batteries (LIBs) have attracted widespread attention as an alternative energy source. Therefore, LiFePO4 has emerged as a mainstream cathode material due to its low cost, environmental friendliness, excellent thermal stability, and stable discharge potential at 3.4V. Various methods have been developed for synthesizing LiFePO4, including solid-state sintering, hydrothermal / solvothermal methods, sol-gel processing, and spray pyrolysis. From a large-scale production perspective, using iron phosphate as a precursor, adding carbon and lithium sources, and high-temperature solidification has become the mainstream production approach. The morphology and structure of iron phosphate play a crucial role in the performance of lithium iron phosphate.

[0003] The patent "Preparation Method of Composite Structure Ferric Phosphate for High-Capacity, High-Pressure Lithium Iron Phosphate" employs a co-precipitation method. A complexing agent and a template agent are added to an iron-phosphorus mixture, and hydrogen peroxide solution is added at three different rates. The pH is controlled at 3-4 in the first stage, 4-5 in the second stage, and 2-3 in the third stage to obtain a composite structure of flake and granular ferric phosphate. However, this technology ① requires the addition of complexing and template agents, making wastewater treatment difficult; the operation is complex, requiring multiple crystallizations to prepare large-particle ferric phosphate, followed by the preparation of small-particle ferric phosphate from the large-particle ferric phosphate slurry. Particle size is difficult to control stably, the particle size distribution ratio of the product does not meet the design value, and the product stability is poor.

[0004] The patent "A Ferric Phosphate Material and Its Preparation Method and Application" uses a multiple crystallization method to prepare large-particle phosphate and a co-precipitation method to prepare small-particle ferric phosphate, controlling the ratio of large and small particles to prepare ferric phosphate with high vibration density and a good balance of large and small particles. However, the small particles are generated in the existing large-particle ferric phosphate slurry, which can lead to further growth of the large-particle ferric phosphate, making it impossible to control the size and ratio of the large particles.

[0005] The patent "A Method for Preparing High-Capacity Lithium Iron Phosphate with High Plunge Density" describes a method for preparing doped lithium iron phosphate dihydrate by adding dopants (titanium sulfate, magnesium sulfate, ammonium metavanadate, manganese sulfate, niobium oxalate) and phosphate salts to divalent iron, along with hydrogen peroxide. A flux of FP+ dihydrate is used, and the water of crystallization is removed at high temperature to prepare large single-crystal lithium iron phosphate with a diameter of 0.5-2 μm. Doping provides the electrical properties, and the compaction density is 2.60 g / cm³. 30.1C 161mAh / g, but because the large single crystal iron phosphate was prepared by adding flux, the number of small particles in the iron phosphate was insufficient, which affected the compaction of lithium iron phosphate and further improvement of its electrical performance.

[0006] However, the above technologies have the following drawbacks: 1. Complexing agents and template agents need to be added, making wastewater treatment difficult; the operation is complicated, requiring multiple crystallizations to prepare large-particle ferric phosphate, and then preparing small-particle ferric phosphate in the large-particle ferric phosphate slurry. The particle size is difficult to control stably, the particle size distribution ratio of the product does not meet the design value, and the product stability is poor. 2. The high pH of the process reaction makes it easy for iron ions to hydrolyze and form ferric hydroxide precipitate. In the ferric phosphate precipitation reaction, Fe(OH)3 will react with FePO4 to form Fe3PO7, which reduces the purity of the ferric phosphate product. 3. The preparation of large-particle iron phosphate cannot effectively produce small-particle iron phosphate. For example, in the patent "A method for preparing high-capacity lithium iron phosphate with high pressure density", large single-crystal iron phosphate is prepared by using a co-solvent, but the number of small-particle iron phosphate in the iron phosphate cannot be guaranteed. Summary of the Invention

[0007] A method for preparing high-compact and high-electrical-performance iron phosphate includes the following steps: Step S1: Prepare iron salt solution A, iron salt solution B, phosphate salt solution A, and phosphate salt solution B; Step S2: Add a large ionic radius dopant A to iron salt solution A to obtain doped iron salt solution A; add a small ionic radius dopant B to iron salt solution B to obtain doped iron salt solution B; add an oxidant to phosphorus salt solution A to obtain a phosphorus-oxygen mixed solution C. Step S3: The doped iron salt solution A and the phosphorus-oxygen mixed solution C are added to the reactor at a first rate to generate large-particle basic iron phosphate intermediate A; then the doped iron salt solution B and the phosphorus salt solution B are added to the reactor at a second rate to generate small-particle basic iron phosphate intermediate B, thus obtaining a mixed slurry of large and small particles D. Step S4: Keep the mixed slurry D of large and small particles at 80-95℃ for 30-240 minutes to obtain white slurry E; Step S5: Wash, dry, calcine, demagnetize, and sieve the white slurry E to obtain high-pressure battery-grade iron phosphate.

[0008] Furthermore, the iron salt solution A is a ferrous salt solution, which is a 0.3-0.5 mol / L FeSO4 solution; the iron salt solution B is a ferric salt solution, which is a 1.5-1.6 mol / L Fe2(SO4)3 solution. The phosphate salt solution A is a 0.3-0.5 mol / L NaH2PO4 solution; The phosphate salt solution B is a NaH2PO4 solution with a concentration of 1.5-1.6 mol / L.

[0009] Furthermore, in step (2), the large ionic radius dopant A is Na with a large ionic radius. + K + Ca 2+ 、Sr 2+ Mn 2+ Cu 2+ La 3+ Metal ion salts; small ionic radius dopant B is a small ionic radius Ti 4+ V 3+ Cr 3+ Mn 4+ Co 3+ Ni 3+ Al 3+ Ga 3+ ,Sc 3+ The metal ion salt; the amount of the large ionic radius dopant A added is 0.1-1% of the mass of the finished iron phosphate; the amount of the small ionic radius dopant B added is 0.1-1% of the mass of the finished iron phosphate.

[0010] Furthermore, in step S2, the oxidant is any one of ozone, H2O2, NaClO, Na2O2, or HClO4.

[0011] Furthermore, in step S3, the first speed is 3-8 m. 3 / h; the second rate is 18-30 m / h. 3 / h.

[0012] Furthermore, in step S5, the washing continues until the conductivity is below 5000 μs / cm.

[0013] Furthermore, step (3) also includes adding a third iron salt solution and a third phosphorus salt solution to the reactor after adding the doped iron salt solution A and the phosphorus oxygen mixed solution C, and before adding the doped iron salt solution B and the phosphorus salt solution B.

[0014] Furthermore, the third phosphate salt solution is a NaH2PO4 solution with a concentration of 1.2 mol / L; the third iron salt solution is a FeSO4 solution with a concentration of 1.2 mol / L.

[0015] Furthermore, the feeding rate of the third iron salt solution and the third phosphate salt solution is 8-18 m. 3 / h.

[0016] Furthermore, after adding the third iron salt solution and the third phosphorus oxygen solution, the iron concentration in the mixture of the third iron salt solution and the third phosphorus oxygen solution is 1.0-1.5 mol / L, and the phosphorus concentration is 1.0-1.5 mol / L.

[0017] This invention prepares high-compact and high-electrical-performance ferric phosphate, while simultaneously maintaining both large and small ferric phosphate particles. The preparation method is simple, requires no additional additives, and is suitable for industrial production.

[0018] This invention aims to prepare a high-compact and high-electrical-performance iron phosphate, characterized by: ① the iron phosphate particles containing three types—large, medium, and small—are combined to form high-compact iron phosphate; ② the size of the iron phosphate particles is controllable, the preparation scheme is simple, no additional additives are required, and it is suitable for industrial production; ③ iron phosphate can improve the low ionic conductivity of lithium iron phosphate, further enhancing its electrical performance.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. By controlling the concentration in multiple stages and adjusting the particle size distribution (combining large, medium, and small particles), the prepared iron phosphate material exhibits an optimized particle distribution, which significantly improves the compaction density. The lithium iron phosphate prepared based on this invention has a compaction density greater than 2.55 g / cm³, with a maximum of 2.63 g / cm³.

[0020] 2. This invention utilizes doping with large ionic radii (such as Mn) 2+ 、Sr 2+ ) and small ionic radius (e.g., Ti) 4+ V 5+ The addition of metal ions optimizes the electronic conductivity and lithium-ion diffusion channels of lithium iron phosphate. The 1C specific capacity of lithium iron phosphate prepared by this invention reaches 144.6-147.3 mAh / g. The introduction of dopants effectively improves the ionic conductivity of the material, thereby enhancing rate performance and cycle stability.

[0021] 3. This invention eliminates the need for complexing agents or template agents, reducing wastewater treatment difficulty and making the process more environmentally friendly. It utilizes staged feeding (the first feeding rate is 3-8 m / s). 3 / h; the second rate is 18-30 m / h. 3 With the design of concentration gradients (iron salt solution A 0.3-0.5 mol / L, iron salt solution B 1.5-1.6 mol / L), precise control of particle size can be achieved, making it suitable for large-scale production.

[0022] 4. In this invention: ① The raw material concentration is divided into high, medium and low concentrations; by adjusting the concentration of raw materials (such as iron salts and phosphates), the reaction rate and crystallization process can be controlled; high concentration: promotes rapid nucleation, generates small particles, which is beneficial to improving the specific surface area and reactivity of the material; medium concentration: optimizes crystal growth and forms a uniform particle distribution; low concentration: promotes particle growth and forms large particles of iron phosphate. ② Iron salt raw materials are divided into iron salts with two ionic valence states: divalent iron and trivalent iron; Fe 2+ It has strong reducing properties and readily reacts with phosphates to form iron phosphate, Fe. 3+ It has strong oxidizing power, directly producing iron phosphate with high product purity. Optimizing the valence state ratio of iron salts can improve the structural stability and electrochemical performance of iron phosphate. In addition, Fe... 3+ Ionic radius (0.645 Å) < Fe 2+ The ionic radius (0.78 Å) can further promote the formation of small-particle iron phosphate; ③ Control the molar ratio of raw materials with different concentrations: By controlling the molar ratio of different concentrations, the relative proportions of large, medium and small ferric phosphate particles are precisely controlled, the proportion of different particles is optimized, and the particles are graded to obtain high-pressure compacted ferric phosphate. ④ Ferric phosphate is doped with multiple metal ions: metal ions (such as Mn) 2+ Ti 4+ V 5+ ... can introduce additional electrons or holes to improve the electronic conductivity of the material; in addition, doping with metal ions can expand the lithium-ion diffusion channels, increase the ion diffusion rate, improve the lithium iron phosphate ion conductivity, and improve the electrical performance of the material. Attached Figure Description

[0023] Figure 1 The microstructure of high-pressure iron phosphate prepared in Example 1; Figure 2 The microstructure of iron phosphate prepared in Comparative Example 1; Figure 3 The particle size distribution diagrams are for the iron phosphate PSD prepared in Example 1 and Comparative Example 1. Detailed Implementation

[0024] Example 1 A method for preparing high-compact and high-electrical-performance iron phosphate includes the following steps: (1) Prepare 0.5 mol / L FeSO4 ferrous solution A and 1.6 mol / L Fe2(SO4)3 ferric solution B; prepare 0.5 mol / L NaH2PO4 solution A and 1.6 mol / L NaH2PO4 solution B, add hydrogen peroxide solution with a molar amount of 0.6 times that of iron salt to phosphate salt solution A, mix well and set aside for use; (2) Add 0.5% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to FeSO4 solution A and dissolve it completely; add 0.5% (relative to the mass ratio of the finished iron phosphate) of Ti(SO4)2 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt B is 6 times that of iron salt A. Yellow mixed slurry D is obtained. (4) The yellow mixed slurry D is heated to 90℃ at a uniform rate and kept at the temperature for 60 min before being discharged. The white slurry E is filtered and washed by a plate and frame filter press. The conductivity is controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder is fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature is set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle is 1℃, and the transmission frequency is 15Hz. After calcination, high-performance doped modified ferric phosphate is prepared, with a tap density of 1.38 g / cm³. 3 The comparison value is 10.38cm. 2 / g, with a large particle size of 578 nm and a small particle size of 89 nm, and a large particle to small particle ratio of approximately 1:6. The dopant content is 476 ppm Mn and 489 ppm Ti.

[0025] Example 2 The difference between this embodiment and Embodiment 1 lies in the reaction concentration, as detailed below: A method for preparing high-compact and high-electrical-performance iron phosphate includes the following steps: (1) Prepare 0.3 mol / L FeSO4 solution A and 1.5 mol / L Fe2(SO4)3 solution B; prepare 0.3 mol / L NaH2PO4 solution A and 1.5 mol / L NaH2PO4 solution B. Add hydrogen peroxide solution with a molar amount of 0.60 times that of iron salt to phosphate salt solution A, mix well and set aside for use. (2) Add 0.5% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to FeSO4 solution A and dissolve it completely; add 0.5% (relative to the mass ratio of the finished iron phosphate) of Ti(SO4)2 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt B is 6 times that of iron salt A. Yellow mixed slurry D is obtained. (4) The yellow mixed slurry D is heated to 90℃ at a uniform rate and kept at the temperature for 60 min before being discharged. The white slurry E is filtered and washed by a plate and frame filter press. The conductivity is controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder is fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature is set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle is 1℃, and the transmission frequency is 15Hz. After calcination, high-performance doped modified ferric phosphate is prepared, with a tap density of 1.36 g / cm³. 3 The ratio is 9.28 cm. 2 / g, with a large particle size of 653 nm and a small particle size of 95 nm, and a large particle to small particle ratio of approximately 1:6. The doping element Mn content is 482 ppm and Ti content is 491 ppm.

[0026] Example 3 The difference between this embodiment and Embodiment 1 is that the iron salt solution B is 5 times the volume of the iron salt solution A, as detailed below: A method for preparing high-compact and high-electrical-performance iron phosphate includes the following steps: (1) Prepare 0.5 mol / L FeSO4 solution A and 1.6 mol / L Fe2(SO4)3 solution B; prepare 0.5 mol / L NaH2PO4 solution A and 1.6 mol / L NaH2PO4 solution B, add hydrogen peroxide solution with a molar amount of 0.6 times that of iron salt to phosphate salt solution A, mix well and set aside for use; (2) Add 0.5% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to FeSO4 solution A and dissolve it completely; add 0.5% (relative to the mass ratio of the finished iron phosphate) of Ti(SO4)2 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt B is 6 times that of iron salt A. Yellow mixed slurry D is obtained. (4) The yellow mixed slurry D was heated to 90℃ at a constant rate and kept at that temperature for 60 min before being discharged. The white slurry E was filtered and washed by a plate and frame filter press. The conductivity was controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder was fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature was set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle was 1℃, and the transmission frequency was 15Hz. After calcination, high-performance doped modified ferric phosphate was prepared, with a tap density of 1.24 g / cm³. 3 The ratio is 9.75 cm. 2 / g, with a large particle size of 492 nm and a small particle size of 95 nm, and a large particle to small particle ratio of approximately 1:5. The doping element Mn content is 495 ppm and Ti content is 488 ppm.

[0027] Example 4 The difference between this embodiment and Embodiment 1 is that dopant A is SrSO4 and dopant B is NH4VO3.

[0028] A method for preparing high-compact and high-electrical-performance iron phosphate includes the following steps: (1) Prepare 0.5 mol / L FeSO4 solution A and 1.6 mol / L Fe2(SO4)3 solution B; prepare 0.5 mol / L NaH2PO4 solution A and 1.6 mol / L NaH2PO4 solution B. Add hydrogen peroxide solution with a molar amount of 0.6 times that of iron salt to phosphate salt solution A, mix well and set aside for use. (2) Add 0.6% (relative to the mass ratio of the finished iron phosphate) of SrSO4 solid to FeSO4 solution A and dissolve it completely; add 0.6% (relative to the mass ratio of the finished iron phosphate) of NH4VO3 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt B is 6 times that of iron salt A. Yellow mixed slurry D is obtained. (4) The yellow mixed slurry D is heated to 90℃ at a uniform rate and kept at the temperature for 60 min before being discharged. The white slurry E is filtered and washed by a plate and frame filter press. The conductivity is controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder is fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature is set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle is 1℃, and the transmission frequency is 15Hz. After calcination, high-performance doped modified ferric phosphate is prepared, with a tap density of 1.34 g / cm³. 3 The ratio is 10.54 cm. 2 / g, with a large particle size of 578nm and a small particle size of 89nm, and a large particle to small particle ratio of approximately 1:6. The dopant element content is 586ppm for Sr and 578ppm for V.

[0029] Example 5 The difference between this embodiment and Embodiment 1 is that a third iron salt solution and a third phosphorus-oxygen mixture are added.

[0030] A method for preparing high-compact and high-electrical-performance iron phosphate includes the following steps: (1) Prepare 0.5 mol / L FeSO4 solution A, 1.6 mol / L Fe2(SO4)3 solution B and 1.2 mol / L third iron salt solution; prepare 0.5 mol / L NaH2PO4 solution A, 1.6 mol / L NaH2PO4 solution B and 1.2 mol / L third phosphate salt solution, add hydrogen peroxide solution with a molar amount of 0.6 times that of iron salt to the above phosphate salt solutions, mix well and set aside for use; (2) Add 0.6% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to FeSO4 solution A and dissolve it completely; add 0.6% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to the third iron salt solution and dissolve it completely; add 0.6% (relative to the mass ratio of the finished iron phosphate) of NH4VO3 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, a third iron salt solution and a third phosphate salt solution are added to the reactor. The addition is completed in 30 minutes. The molar amount of iron salt in the third solution is twice that of iron salt A. Then, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt B is six times that of iron salt A. A yellow mixed slurry D is obtained. (4) The yellow mixed slurry D is heated to 90℃ at a uniform rate and kept at the temperature for 60 min before being discharged. The white slurry E is filtered and washed by a plate and frame filter press. The conductivity is controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder is fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature is set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle is 1℃, and the transmission frequency is 15Hz. After calcination, high-performance doped modified ferric phosphate is prepared, with a tap density of 1.42 g / cm³. 3 The ratio is 11.29 cm. 2 / g, with large particles of 578nm, medium particles of 328nm, and small particles of 89nm, and a ratio of large, medium, and small particles of approximately 1:2:6. The dopant content is 1129 ppm for Mn and 578 ppm for V.

[0031] Comparative Example 1 The difference between this comparative example and Example 1 is that the concentrations of iron salt A and iron salt B are the same, and the concentrations of phosphate salt A and phosphate salt B are the same, as detailed below: A method for preparing ferric phosphate includes the following steps: (1) Prepare 1 mol / L FeSO4 solution A and 1 mol / L Fe2(SO4)3 solution B; prepare 1 mol / L NaH2PO4 solution A and 1 mol / L NaH2PO4 solution B. Add hydrogen peroxide solution with 0.6 times the molar amount of iron salt to phosphate salt solution A, mix well and set aside for use. (2) Add 0.5% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to FeSO4 solution A and dissolve it completely; add 0.5% (relative to the mass ratio of the finished iron phosphate) of Ti(SO4)2 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt A is 6 times that of iron salt B, and a yellow mixed slurry D is obtained. (4) The yellow mixed slurry D is heated to 90℃ at a uniform rate and kept at the temperature for 60 min before being discharged. The white slurry E is filtered and washed by a plate and frame filter press. The conductivity is controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder is fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature is set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle is 1℃, and the transmission frequency is 15Hz. After calcination, high-performance doped modified ferric phosphate is prepared, with a tap density of 1.03 g / cm³. 3 The ratio is 8.95 cm. 2 / g, with particle size distribution ranging from 1.0 to 1.5 μm, containing 452 ppm Mn and 469 ppm Ti as dopants.

[0032] Comparative Example 2 The difference between this comparative example and Example 1 is that the ferric salt solution B is a ferrous solution, as detailed below: A method for preparing ferric phosphate includes the following steps: (1) Prepare 0.5 mol / L FeSO4 solution A and 1.6 mol / L FeSO4 solution B; prepare 0.5 mol / L NaH2PO4 solution A and 1.6 mol / L NaH2PO4 solution B. Add hydrogen peroxide solution with a molar amount of 0.6 times that of iron salt to phosphate salt solutions A and B, mix well and set aside for use. (2) Add 0.5% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to FeSO4 solution A and dissolve it completely; add 0.5% (relative to the mass ratio of the finished iron phosphate) of Ti(SO4)2 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt B is 6 times that of iron salt A. Yellow mixed slurry D is obtained. (4) The yellow mixed slurry D is heated to 90℃ at a uniform rate and kept at the temperature for 60 min before being discharged. The white slurry E is filtered and washed by a plate and frame filter press. The conductivity is controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder is fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature is set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle is 1℃, and the transmission frequency is 15Hz. After calcination, high-performance doped modified ferric phosphate is prepared, with a tap density of 1.17 g / cm³. 3 The specific gravity is 8.86 cm. 2 / g, with a large particle size of 578 nm and a small particle size of 180 nm, and a large particle to small particle ratio of approximately 1:6. The doping element Mn content is 462 ppm and Ti content is 453 ppm.

[0033] Comparative Example 3 The difference between this comparative example and Example 1 is that dopants A and B were not added to the raw materials, as detailed below: A method for preparing ferric phosphate includes the following steps: (1) Prepare 0.5 mol / L FeSO4 solution A and 1.6 mol / L Fe2(SO4)3 solution B; prepare 0.5 mol / L NaH2PO4 solution A and 1.6 mol / L NaH2PO4 solution B. Add hydrogen peroxide solution with a molar amount of 0.6 times that of iron salt to phosphate salt solution A, mix well and set aside for use. (2) Add 0.5% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to FeSO4 solution A and dissolve it completely; add 0.5% (relative to the mass ratio of the finished iron phosphate) of Ti(SO4)2 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt B is 6 times that of iron salt A. Yellow mixed slurry D is obtained. (4) The yellow mixed slurry D is heated to 90℃ at a uniform rate and kept at the temperature for 60 min before being discharged. The white slurry E is filtered and washed by a plate and frame filter press. The conductivity is controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder is fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature is set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle is 1℃, and the transmission frequency is 15Hz. After calcination, high-performance doped modified ferric phosphate is prepared, with a tap density of 1.32 g / cm³. 3 The ratio is 9.56 cm. 2 / g, large particle size 487 nm, small particle size 123 nm, large particle to small particle ratio approximately 1:6, Mn and Ti content <20ppm.

[0034] Comparative Example 4 The difference between this comparative example and Example 1 is that the molar amount of iron salt B is the same as that of iron salt A, as detailed below: A method for preparing ferric phosphate includes the following steps: (1) Prepare 0.5 mol / L FeSO4 solution A and 1.6 mol / L Fe2(SO4)3 solution B; prepare 0.5 mol / L NaH2PO4 solution A and 1.6 mol / L NaH2PO4 solution B. Add hydrogen peroxide solution with a molar amount of 0.6 times that of iron salt to phosphate salt solution A, mix well and set aside for use. (2) Add 0.5% (relative to the mass ratio of the finished iron phosphate) of MnSO4 solid to FeSO4 solution A and dissolve it completely; add 0.5% (relative to the mass ratio of the finished iron phosphate) of Ti(SO4)2 solid to Fe2(SO4)3 solution B and dissolve it completely. (3) Iron salt solution A and phosphate salt solution A are added to the reactor simultaneously. The addition is completed in 60 minutes. After the addition of iron salt and phosphate salt solution A, iron salt solution B and phosphate salt solution B are added to the reactor. The addition is completed in 10 minutes. The molar amount of iron salt A is the same as that of iron salt B, and a yellow mixed slurry D is obtained. (4) The yellow mixed slurry D is heated to 90℃ at a uniform rate and kept at the temperature for 60 min before being discharged. The white slurry E is filtered and washed by a plate and frame filter press. The conductivity is controlled to be <5000μs / cm during the process to obtain ferric phosphate dihydrate filter cake. (5) The filter cake is conveyed to the flash evaporator by belt, the feed screw frequency is 15Hz, the outlet air temperature is controlled at 155℃, the main stirring frequency is 80 Hz, the free water in the ferric phosphate dihydrate filter cake is removed, and the filter cake is crushed to obtain ferric phosphate dihydrate powder. (6) Ferric phosphate dihydrate powder is fed into a rotary kiln at a uniform speed through a feed screw. The kiln temperature is set to 300℃-400℃-500℃-660℃-660℃-660℃-520℃, the kiln inclination angle is 1℃, and the transmission frequency is 15Hz. After calcination, high-performance doped modified ferric phosphate is prepared, with a tap density of 0.97 g / cm³. 3 The comparison value is 7.56cm. 2 / g, with a large particle size of 589 nm and a small particle size of 102 nm, and a large particle to small particle ratio of approximately 1:1. The doping element Mn content is 479 ppm and Ti content is 498 ppm.

[0035] Experimental Section

[0036] Experiment 1 The anhydrous iron phosphate prepared in Examples 1-4 and Comparative Examples 1-4 of the present invention was further used to prepare lithium iron phosphate materials, including the following steps: S1: The iron phosphate materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 of this invention are mixed with lithium carbonate, glucose, polyethylene glycol and a grinding conductive agent in a mass ratio of 7.23:2.10:0.07:0.02:0.022. 0.06% titanium oxide by weight of iron phosphate is added, and then the mixture is coarsely ground and finely ground until D50 reaches 400 nm. S2: Prepare spherical precursors by spray drying the finely ground slurry; S3: Add the spherical precursor to the planetary ball mill and crush for 20 minutes; S4: Sinter the crushed precursor at 780℃ for 8 hours; S5: The sintered lithium iron phosphate material is crushed, graded, and demagnetized to obtain high-pressure lithium iron phosphate.

[0037] The lithium iron phosphate materials prepared from the anhydrous iron phosphate prepared in Examples 1-5 and Comparative Examples 1-4 of this invention have compaction densities and electrical properties as shown in Table 1.

[0038] Table 1 Compacted density and electrical properties results

[0039] As shown in Table 1, the compacted density of lithium iron phosphate materials prepared based on anhydrous iron phosphate prepared in Examples 1 to 4 is greater than 2.55 g / cm³. 3However, the iron phosphate prepared based on Comparative Examples 1-4 cannot simultaneously achieve both high compaction and high electrical performance. This is because the iron phosphate prepared using this invention has a reasonable distribution of large, medium, and small particle sizes and quantities. Large iron phosphate particles sinter to form large lithium iron phosphate particles, medium iron phosphate particles sinter to form large lithium iron phosphate particles, and small iron phosphate particles sinter to form small lithium iron phosphate particles. The small and medium lithium iron phosphate particles fully fill the gaps between the large lithium iron phosphate particles to form high-compact lithium iron phosphate. Simultaneously, the large and medium iron phosphate particles are doped with a higher proportion of Fe. 3+ Metal ions with large ionic radii are more likely to be incorporated into small-particle iron phosphate than Fe. 3+ Metal ions with small ionic radii further optimize the particle size of large, medium and small particles. Multiple metal ions are simultaneously incorporated into the iron phosphate lattice to improve the low conductivity of lithium iron phosphate ions. Therefore, using iron phosphate particles of various sizes doped with multiple metals as precursors for lithium iron phosphate can balance high compaction density and electrochemical performance.

[0040] Experiment 2 SEM images of the ferric phosphate prepared in Example 1 and Comparative Example 1 were analyzed, and the results are shown below. Figure 1-2 , Figure 1 The microstructure of high-pressure ferric phosphate with typical particle size combinations prepared in Example 1 of this invention is shown. Figure 2 The microstructure of the typical conventional battery-grade iron phosphate prepared in Comparative Example 1 of this invention is shown.

[0041] from Figure 1 As can be seen from the above, this invention, through multi-stage raw material concentration control, iron ion valence state control, and doping technology, can prepare iron phosphate battery materials with large, medium, and small particles coexisting in a co-precipitation system. The lithium iron phosphate material prepared using this precursor has a compaction rate of 2.61 g / cm³. 3 1C discharge capacity: 145.3 mAh / g (Table 1).

[0042] from Figure 2 It can be seen that Comparative Example 1 cannot produce a lithium iron phosphate material with a combination of large, medium, and small particles. The primary particle sizes are similar, and there is no morphological characteristic of a combination of large and small particles. The lithium iron phosphate material prepared using this precursor has a compaction strength of 2.48 g / cm³. 3 1C discharge capacity: 138.23 mAh / gg (Table 1).

[0043] Experiment 3 The Fe, P, Mn, Ti, Fe / P, BET, D10, D50, D90, and D100 values ​​of the iron phosphate materials prepared in Example 1 and Comparative Example 1 were tested. The results are shown in Table 2. The Fe / P ratio of Example 1 is higher than that of Comparative Example 1 because Example 1 contains large-particle iron phosphate with a high iron-to-phosphorus ratio. The specific surface area of ​​large-particle iron phosphate is lower than that of small-particle iron phosphate, therefore the specific surface area is slightly lower than that of Comparative Example 1. Example 1 contains both Mn and Ti doping elements, while Comparative Example 1 does not contain either Mn or Ti. The presence of Mn and Ti can promote the formation of large and small particles, respectively, and simultaneously improve electrical properties. Combining the particle size data and particle size distribution diagram, it can be found that ( Figure 3 Example 1 shows a bimodal particle size distribution, while Comparative Example 1 shows a single peak, indicating that the iron phosphate in Example 1 is a high-pressure compacted iron phosphate material with a combination of large and small particles; Comparative Example 1 shows a single-peak distribution, with particle size concentrated in a narrow range and lacking multi-scale particle distribution.

[0044] Table 2 Comparison of the properties of iron phosphate prepared in Example 1 and Comparative Example 1 .

Claims

1. A method for preparing high-compact and high-electrical-performance iron phosphate, characterized in that, Includes the following steps: Step S1: Prepare iron salt solution A, iron salt solution B, phosphate salt solution A, and phosphate salt solution B; Step S2: Add a large ionic radius dopant A to the iron salt solution A to obtain a doped iron salt solution A; Adding a small ionic radius dopant B to an iron salt solution B yields a doped iron salt solution B; adding an oxidant to a phosphorus salt solution A yields a phosphorus-oxygen mixed solution C. Step S3: The doped iron salt solution A and the phosphorus-oxygen mixed solution C are added to the reactor at the first rate to generate large-particle basic iron phosphate intermediate A; Subsequently, the doped iron salt solution B and phosphate salt solution B were added to the reactor at a second rate to generate small-particle basic iron phosphate intermediate B, resulting in a mixed slurry of large and small particles D. Step S4: Keep the mixed slurry D of large and small particles at 80-95℃ for 30-240 minutes to obtain white slurry E; Step S5: Wash, dry, calcine, demagnetize, and sieve the white slurry E to obtain high-pressure battery-grade iron phosphate.

2. The method for preparing high-compact and high-electrical-performance iron phosphate as described in claim 1, characterized in that, The iron salt solution A is a 0.3-0.5 mol / L FeSO4 solution; the iron salt solution B is a 1.5-1.6 mol / L Fe2(SO4)3 solution; the phosphate salt solution A is a 0.3-0.5 mol / L NaH2PO4 solution; the phosphate salt solution B is a 1.5-1.6 mol / L NaH2PO4 solution.

3. The method for preparing high-compact and high-electrical-performance iron phosphate according to claim 1, characterized in that, In step (2), the large ionic radius dopant A is Na with a large ionic radius. + K + Ca 2+ 、Sr 2+ Mn 2+ Cu 2+ La 3+ Metal ion salts; small ionic radius dopant B is a small ionic radius Ti 4+ V 3+ Cr 3+ Mn 4+ Co 3+ Ni 3+ Al 3+ Ga 3+ ,Sc 3+ The metal ion salt; the amount of the large ionic radius dopant A added is 0.1-1% of the mass of the finished iron phosphate; the amount of the small ionic radius dopant B added is 0.1-1% of the mass of the finished iron phosphate.

4. The method for preparing high-pressure and high-electrical-performance iron phosphate according to claim 1, characterized in that: In step S2, the oxidant is any one of ozone, H2O2, NaClO, Na2O2, or HClO4.

5. The method for preparing high-pressure and high-electrical-performance iron phosphate according to claim 1, characterized in that, In step S3, the first speed is 3-8 m. 3 / h; the second rate is 18-30 m / h. 3 / h.

6. The method for preparing high-pressure and high-electrical-performance iron phosphate according to claim 1, characterized in that, In step S5, the washing continues until the conductivity is below 5000 μs / cm.

7. The method for preparing high-pressure and high-electrical-performance iron phosphate according to claim 1, characterized in that, Step (3) also includes adding a third iron salt solution and a third phosphorus salt solution to the reactor after adding the doped iron salt solution A and the phosphorus oxygen mixed solution C, and before adding the doped iron salt solution B and the phosphorus salt solution B.

8. The method for preparing high-pressure and high-electrical-performance iron phosphate according to claim 7, characterized in that, The third phosphate salt solution is a 1.2 mol / L NaH2PO4 solution; the third iron salt solution is a 1.2 mol / L FeSO4 solution.

9. The method for preparing high-pressure and high-electrical-performance iron phosphate according to claim 7, characterized in that, The feeding rate of the third iron salt solution and the third phosphate salt solution is 8-18 m. 3 / h.

10. The method for preparing high-pressure and high-electrical-performance iron phosphate according to claim 7, characterized in that, After adding the third iron salt solution and the third phosphorus oxygen solution, the iron concentration in the mixture of the third iron salt solution and the third phosphorus oxygen solution is 1.0-1.5 mol / L and the phosphorus concentration is 1.0-1.5 mol / L.